2022
DOI: 10.1002/adfm.202201020
|View full text |Cite
|
Sign up to set email alerts
|

Organic Ion Template‐Guided Solution Growth of Ultrathin Bismuth Oxyselenide with Tunable Electronic Properties for Optoelectronic Applications

Abstract: 2D Bi2O2Se has recently attracted widespread research interest due to its high electron mobility and good air stability with tunable bandgap. However, the direct and controllable growth of large‐size, high‐quality ultrathin Bi2O2Se with tunable electronic properties remains a great challenge. Here, an organic ion template‐guided solution growth method, is developed using water as a solvent to efficiently obtain high‐quality 2D Bi2O2Se. Significantly, the thicknesses and morphologies of 2D Bi2OxSe with various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Previous studies reported that the theoretical work function of Bi 2 O 2 Se is 4.23 eV (2 Layer) and 4.15 eV (1L), whereas the experimental value varies between 4.37 and 4.45 eV. In contrast, we find the work function of Bi 2 O 2 Se as 5.485 eV, which is much higher. This is attributed to the trapping of the electron in the defect states in Bi 2 O 2 Se and the corresponding movement of the Fermi level away from the conduction band minimum ( E CBM ) and, thus, the increase in work function . Similarly, the work function of 1L-MoS 2 is 4.435 eV, as reported in our previous study …”
Section: Resultssupporting
confidence: 77%
“…Previous studies reported that the theoretical work function of Bi 2 O 2 Se is 4.23 eV (2 Layer) and 4.15 eV (1L), whereas the experimental value varies between 4.37 and 4.45 eV. In contrast, we find the work function of Bi 2 O 2 Se as 5.485 eV, which is much higher. This is attributed to the trapping of the electron in the defect states in Bi 2 O 2 Se and the corresponding movement of the Fermi level away from the conduction band minimum ( E CBM ) and, thus, the increase in work function . Similarly, the work function of 1L-MoS 2 is 4.435 eV, as reported in our previous study …”
Section: Resultssupporting
confidence: 77%
“…66 In the NS with defects, the work function is higher than for the pure Bi 2 O 2 Se bulk, and the Fermi level moves away from the CB, suggesting that the nanosheet becomes less n-type, which is attributed to defect-induced trapping. 67 To explain the PNPC effect, we propose the band diagrams shown in Fig. 5d–f that illustrate the different processes taking place in the absence and presence of light.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the band structure of the SnO 2 and WO 3 , UV–vis and the small binding energy range scan of VB-XPS were carried out to obtain the band gap ( E g ), conduction band ( E c ), and valence band ( E v ). The band gap was calculated by the Tauc plot method, as shown in Figure S6a, b, and the E g values of SnO 2 and WO 3 are 3.31 and 2.85 eV, respectively. Figure S6c,d shows the VB-XPS results of SnO 2 and WO 3 ; Δ V is the distance between the two inflection points of the curve, and it is also equal to the distance from the top of the E c to the Fermi level; meanwhile, the work function (Φ) and Δ V have the following relationship: Δ V = Φ - ψ, ψ is the work function of the XPS analyzer. , As a result, the E c and E v of SnO 2 and WO 3 were calculated to be −4.45 and −7.76, −3.99, and – 6.84 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The band gap was calculated by the Tauc plot method, as shown in Figure S6a, b, and the E g values of SnO 2 and WO 3 are 3.31 and 2.85 eV, respectively. Figure S6c,d shows the VB-XPS results of SnO 2 and WO 3 ; Δ V is the distance between the two inflection points of the curve, and it is also equal to the distance from the top of the E c to the Fermi level; meanwhile, the work function (Φ) and Δ V have the following relationship: Δ V = Φ - ψ, ψ is the work function of the XPS analyzer. , As a result, the E c and E v of SnO 2 and WO 3 were calculated to be −4.45 and −7.76, −3.99, and – 6.84 eV, respectively. Then, the differences in E c (Δ E c ) and E v (Δ E v ) between SnO 2 and WO 3 are 0.46 and 0.92 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%